Selling sex in the Reich: prostitutes in German society, 1914 - 1945 - Harris, Victoria (Oxford University Press)
Rescuing the fallen woman -- The prostitute experience -- The prostitute milieu -- The prostitute and society -- The prostitute and the state -- Towards an understanding of the prostitute experience